Prudent versus Imprudent Lending to Africa From debt relief to emerging lenders - Reisen, Helmut (OECD Development Centre Working Papers, 2008)
Over recent years, a number of emerging creditors have increased their aid and lending to Africa's Low-Income Countries (LICs). This has fed worries that new official lenders may be undoing years of international efforts to rein in over-indebtedness in Africa, to reduce the continent's exposure to foreign-currency denominated debt and to encourage good governance by making loans conditional on political and economic reforms. These worries are reflected in the G8 Action Plan for Good Financial Governance in Africa, which attempts to include emerging lenders in the DSF framework - the Joint Bank-Fund Debt Sustainability Framework. The empirical analysis of debt dynamics distinguishes three country groups: African HIPC, HIPC-China (High China Presence), and Resource-rich IDA-only. All groups display marked trends of lower debt ratios (in net present value terms, NPV), in most cases below debtdistress level for even the lowest governance groups. Evidence on links between growth and lending may even suggest that African HIPC are currently under-leveraged. Generally, there is very little evidence of "imprudent lending" to debt relief beneficiaries in the figures up to 2006. The Asian giants lower debt ratios a little through debt relief, but they do this even more through stimulating exports and growth. This holds in particular for those countries towards which their lending is mostly directed: the resource-rich countries, rather than the debt-relief beneficiaries